Analisis Feedback dalam Pembinaan Atlet Bola Voli Putri - Yuan Darazatzati; Anggit Wicaksono (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to assess coach feedback to athletes during training at a women's volleyball club in Semarang Regency. This study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Snowball sampling was used to obtain informants, namely two coaches and six athletes. The study findings show that coach feedback has a positive impact on the technical development and mental state of female athletes. Athletes experienced increased motivation, self-confidence, and a clearer understanding of errors. Specific feedback helped athletes improve their performance and potentially improved match results. The results showed that feedback was provided routinely, generally in the form of direct correction. Athletes tended to be able to understand these directions well, especially when delivered clearly. Overall, feedback was proven to contribute positively to athlete motivation and confidence.